MANAGEMENT OF IN-PATIENTS WITH UNCONTROLLED ARTERIAL HYPERTENSION - I. V. Logacheva (Российский кардиологический журнал, 2014)
Aim. To investigate the antihypertensive effectiveness of a fixed perindopril/ amlodipine combination (Prestans) and its effects on the visit-to-visit variability of blood pressure levels and quality of life (QoL) among in-patients with uncontrolled arterial hypertension (AH).Material and methods. The study included 35 patients (15 men and 20 women; mean age 50,4±8,9 years) who were hospitalised due to uncontrolled AH. The previously administered ineffective antihypertensive therapy was cancelled and replaced by Prestans (5/5, 10/5, 5/10, or 10/10 mg/day, subject to AH severity). The in-hospital monitoring lasted for 14 days and included daily assessment of office, systolic and diastolic BP (SBP, DBP), mean and pulse BP, intra-visit and visit- to-visit BP variability, and QoL (SF-36 questionnaire).Results. All hospitalised patients had Stage III AH, including 31,4% with Degree 2 AH and 68,6% with Degree 3 AH. During the in-hospital course of Prestans treatment, the levels of SBP and DBP decreased from 184,2±14,6 to 142,1±13,8 mm Hg (p<0,05) and from 104,6±7,2 to 84,3±5,7 mm Hg (p<0,05), respectively. Mean and pulse BP levels also reduced significantly. The intra-visit variability of office SBP significantly decreased from Day 1 (5,07±0,9 mm Hg) to Day 14 (1,5±0,1 mm Hg; p<0.05). The visit-to-visit SBP variability also decreased, from 11,6±2,5 to - 2,1±1,2 mm Hg, respectively (p<0,01). At baseline, the patients demonstrated a substantial reduction in both physical and mental health QoL parameters. The treatment was associated with a significant improvement in the psychological health domain (emotional and social functioning).Conclusion. In patients with uncontrolled AH, the in-hospital treatment with Prestans resulted in a mean reduction of SBP/DBP levels by 38,4/19,6 mm Hg, a significant decrease in mean and pulse BP levels, and achievement of target BP levels in 82.9% of the patients as early as at Day 14 of the treatment. The amlodipine/perindopril treatment was also associated with reduced intra-visit and visit-to-visit BP variability, as well as with improved BP control, emotional status, and QoL.